Living Standards in Southeast Asia : Changes over the Long Twentieth Century, 1900-2015 - Booth, Anne, 1946-; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2020)
Living Standards in Southeast Asia: Changes over the Long Twentieth Century, 1900-2015 examines changes in living standards across the ten countries of Southeast Asia (Indonesia, Malaysia, Singapore, Philippines, Thailand, Brunei, Myanmar, Vietnam, Cambodia and Laos) from the early years of the 20th century to the early 21st century. It covers both the last decades of the colonial period, the transition to independence and the decades from 1960 to the 2010s. The study uses a range of monetary and non-monetary indicators to assess how living standards have changed over time. It examines the outcomes in the context of debates about economic growth, inequality and poverty alleviation which began in the 1960s and 1970s, and continue to the present.
Assessing changes in living standards in Southeast Asia in the twentieth and early twenty-first centuries -- The colonial period: population and output growth in agricultural and non-agricultural sectors -- The colonial period: measures of welfare and changing living standards -- Confronting the challenges of independence -- Estimating poverty and inequality: country estimates from the 1950s to the 1970s -- The 1980s and the 1990s: the fast and the slow in Southeast Asia -- Growth, poverty and distribution in the early twenty-first century -- Government policy interventions -- What have we learned? -- Bibliography -- Index.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Economic development -- Southeast Asia -- 21st century; Economic development -- Southeast Asia -- 20th century; Southeast Asia -- Social conditions -- 21st century; Southeast Asia -- Social conditions -- 20th century; Southeast Asia -- Economic conditions -- 21st century; Southeast Asia -- Economic conditions -- 20th century; Electronic books